2020
DOI: 10.3390/nu12072042
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Plays More Important Role in Determining Functional State in Older People Living in the Community than in Nursing Home Residents

Abstract: The aim of this study was to verify whether the relationship between nutritional and functional status differs between seniors in the community and those in long-term care institutions. One hundred nursing home (NH) residents aged 60 years and above and 100 sex- and age-matched community-dwelling (CD) older adults were examined. Functional status was assessed using the Comprehensive Geriatric Assessment (CGA) and nutritional status using anthropometric measures, the Mini Nutritional Assessment question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
2
14
2
Order By: Relevance
“…Our sample represented 1.75% of all older adults residing in LTNHs in Gipuzkoa (Basque Country, Northern Spain). Notably, our mean participant age, 86.34 ± 6.77 years, was higher than all other study populations to date on institutionalized older adults including the 2012 European SHELTER study of 57 LTNHs from 7 EU countries and Israel where the mean age of the participants was 83.4 years [42][43][44][45][46][47][48]. The percentage of participants in our study over 90 years of age (36%) was also high compared with other studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Our sample represented 1.75% of all older adults residing in LTNHs in Gipuzkoa (Basque Country, Northern Spain). Notably, our mean participant age, 86.34 ± 6.77 years, was higher than all other study populations to date on institutionalized older adults including the 2012 European SHELTER study of 57 LTNHs from 7 EU countries and Israel where the mean age of the participants was 83.4 years [42][43][44][45][46][47][48]. The percentage of participants in our study over 90 years of age (36%) was also high compared with other studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Nevertheless, the above evidence suggested the high risk of prevalent sarcopenia in nursing-home residents. Institutionalized populations may be more prone to malnutrition [ 89 , 90 ]. A recent cross-sectional study found that malnutrition and physical frailty were highly prevalent among institutionalized older residents and malnutrition was associated with an increased risk of physical frailty among institutionalized Chinese older adults [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the study group was restricted to Central-European community-dwelling older individuals therefore results may be different in other cultures. Correlations of nutritional status and depression may also be different in the institutionalized environments [ 51 , 52 ]. Secondly, no tests were conducted among people with severe dementia or those who were not able to present at the clinic due to mobility problems.…”
Section: Discussionmentioning
confidence: 99%